Peningkatan Proses Pembelajaran Tematik Terpadu menggunakan strategi Active Learning tipe Index Card Match di SD - Melisa Septiani; Elfia Sukma (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
This research is motivated by integrated thematic learning that has not been well implemented, is still in the process of improving. This causes the integrated thematic learning process to be carried out to the maximum. This research purposed to describe the improvement of integrated thematic learnig process using active learning strategi Index Card Match in Elementary School. This research is a classroom action research with qualitative and quantitative approaches. Subjects were teachers and 25 students. This research was consists of two cycles. The first cycle consists of two meetings and the second cycle consists of one meeting with stages of planning, implementation, observation, and reflection . The result of planning observation in cycle I  is 75% (C) and it increase to be 94,44% (SB)  in cycle II. The result of teacher aspect observation in cycle I is 83,35% (B)  and it increase to be 97,22% (SB) in cycle II. The result of student aspect observation in cycle I is 80,55% (C)  and it increase to be 94,44% (SB) in cycle II. The learning outcomes in cycle I is 71,8 (C) and it increase to be 90,62 (SB) in cycle II. The research showed the cooperative learning model Talking Stick type can improve the integrated thematic learnig process in Elementary School